Job Insecurity with Employee Organizational Commitment During The Covid-19 Pandemic at PT. Regional Development Bank of Maluku And North Maluku (Bpdm Malut) - Sherly Charoline Sekewael; Sutarto Wijono (International Journal Labs, 2023)
At this time there are various kinds of changes related to technology and information that are so rapid including the banking world in Indonesia with changes that must make them compete in the corporate world. Likewise, Bank Maluku Malut continues to make changes and technological developments to serve customers better, especially has entered the new normal. The rules made by Bank Maluku Malut in handling the pandemic are expected to be obeyed by all employees. In this case, employees must be required to keep following organizational goals and commit to keep working despite being haunted by anxiety. fear and anxiety about contracting the Covid-19 virus. Therefore, this study aims to determine the relationship between job insecurity and employee organizational commitment during the Covid-19 pandemic at PT. Regional Development Bank of Maluku and North Maluku (BPDM Malut). The method used is quantitative with a correlation design. A total of 31 employees of Bank Maluku Malut who had experienced WFH (Work From Home) were used as research participants using purposive sampling techniques. The research measurement used the Job Insecurity Scale (? = 0.898) and the Organizational Commitment Scale (? = 0.897). The results of this study showed a significant negative relationship between job insecurity and organizational commitment (r = -0.305 and sig. 0.048). That is, the higher the job insecurity, the lower the organizational commitment owned by Bank Maluku Malut employees.